A longitudinal analysis of the effects of open enrollment on equity and academic achievement: Evidence from Minneapolis, Minnesota. (February 2015) - Hong, Saahoon; Choi, Wonseok
Abstract: Open enrollment was expected to provide students in urban school settings with equal opportunity to access schools with abundant educational resources that led to improved student achievement. The One-way ANOVA and Linear Mixed Models used a propensity score matching method were administered to identify to what extent urban students utilized inter-district open enrollment in a Midwestern city and to compare their performances on standardized tests before and after the school transfer had occurred. The results indicated that open enrollment provided black students and students in the child welfare system with equal access to racially and socioeconomically integrated schools. However, these students' academic performance was not significantly enhanced by their open enrollment, except the 3rd grade student achievement in math. The results raised questions about the characteristics of open enrollment. Recommendations for future research are made; study limitations are addressed. Graphical abstract: Note . OE stands for Open Enrollment. Fig. 1. Observed mean scores in the MCA-II math and reading of 3rd and 6th grade cohorts by open enrollment groups (solid lines for the Open Enrollment and dotted lines for the non-OE participants). Highlights: Black students, controlling for the eligibility for free/reduced-price lunch, were more likely to utilize open enrollment in the urban schools. Urban students transferred to schools that had high-performance, a low percentage of minority, low-income, and special education students. Students in the child welfare system equally utilized open enrollment as compared to black students in urban settings. No strong association between open enrollment and achievement score.